Working with Husband? "Occupation's Wife" and Married Women's Employment in the Censuses in England and Wales between 1851 and 1911. Issue 4 (28th September 2020) - You, Xuesheng
Abstract: Women played a vital role in British industrialization. However, studies of women's work are often hindered by data limitation. The British censuses provide an unparalleled opportunity to study women's work and its impact systematically. However, the reliability of the census recording of female employment is still under debate. This articles aims to contribute to this ongoing debate by examining a particular census recording concerning married women who were supposedly working with their husbands, that is "occupation's wife." By analyzing a new source of big data, namely 100 percent sample of Census Enumerators' Books and published census reports, this article shows that the recording of "occupation's wife" was not informative about the level of married women's labor in the form of working together with their husbands in the same trade. Given the important fact that married women recorded as "occupation's wife" constituted the largest group of married women with any occupational titles in the censuses, the results presented in this article suggest a reassessment of some of the empirical foundations in the studies of married women's work.